Utilising Constructed Wetlands From Water Hyacinth for Wastewater Treatment in Oxidation Ponds - Md Latip, Siti Noor Hajjar; Damanhuri, Siti Nur Aida; Ibrahim, Nur Diana; Chin, Khor Bee; Nasruddin, Mimi Fadzlin (International Journal of Integrated Engineering, 2022)
Constructed wetlands are engineered to duplicate the processes occurring in natural wetlands. The main purpose of the structure is to remove contaminants or pollutants from wastewater. Constructed wetland is a new, creative, cost-effective, and green technology compared to conventional treatment systems. Water hyacinth could be cultivated for wastewater treatment and utilised to aid the purification of either industrial wastewater or sewer water. Consequently, the present study was conducted to determine the effects of constructing wetlands with water hyacinth on the wastewater quality of an oxidation pond and the cultivation of water hyacinth as constructed wetlands in an oxidation pond. Floating cages containing water hyacinth plants were monitored for two phases under different wastewater parameters. The data were compared to the Malaysian prescribed Sewage and Industrial Effluent Discharge Standards. The water hyacinth constructed wetlands produced a positive impact and met the requirements for effluent discharge standards.